What It's Worth: Strengthening the Financial Future of Families, Communities and the Nation - Cherie Stueve (Journal of Financial Therapy, 2016)
This book overviews the financial challenges of vulnerable Americans and creative programs that look beyond income as a metric of financial health is divided into four sections. The first section, “Where We Are,” describes the current financial statistics of households by demographic and economic era. The second (and largest) section, “Why Financial Well-Being Matters for All,” is broken into four topics: the economy, financial services system, and community; employment and business; health and social services; and education. Each illustrates the strong role financial well-being plays in other systems at the individual and community level.
Keywords: book review; Federal Reserve Bank; financial well-being